2019
DOI: 10.1161/jaha.118.011664
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Marital Status on the Outcome of Acute Coronary Syndrome: Results From the Acute Coronary Syndrome Israeli Survey

Abstract: Background Marriage is one of the common forms of social support. Conflicting evidence exists about the impact of marital status on the outcomes of patients with acute coronary syndrome ( ACS ). It is further not clear if sex disparity exists in the outcome of married and nonmarried patients with ACS. Methods and Results Data from the ACS Israeli Survey, collected between 2004 and 2016, were used to compare baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…As illustrated in Supplementary Figure 1, 14 potentially eligible studies with a total of 89,176 patients were identified (Table 1) (see Supplementary References 4–7). 110 The risk of bias of each study is summarised in Supplementary Table 1. Extracted and calculated ORs/HRs are listed in Table 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated in Supplementary Figure 1, 14 potentially eligible studies with a total of 89,176 patients were identified (Table 1) (see Supplementary References 4–7). 110 The risk of bias of each study is summarised in Supplementary Table 1. Extracted and calculated ORs/HRs are listed in Table 1.…”
mentioning
confidence: 99%
“…Adjusted ORs for early (one-day, 4 inhospital 6,7 and 30-day (see Supplementary Reference 5)) 8 mortality were available in five studies (see Supplementary Reference 5), 4,68 and adjusted HRs for overall (one-year 8 to 77-month (see Supplementary Reference 6)) mortality were available in eight studies (see Supplementary References 4 and 6). 1,2,5,810…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marriage may affect the development and prognosis of CHD through spouses encouraging each other to adopt healthy lifestyles, seek early medical attention, or comply with treatment regimens, or providing emotional support or financial security 5–7. Previous meta-analyses and population studies reported that married people had lower CHD incidence and mortality and better prognosis after CHD compared with those who were not married 8–12. The association between marriage and the risk of out-of-hospital sudden cardiac arrest has also been reported in previous studies 13 14.…”
Section: Introductionmentioning
confidence: 69%
“…Although marriage is associated with health benefits for both men and women, research has consistently shown that men derive more benefit than women [6]. Marital status may indicate a supportive social environment of the patient with acute coronary syndrome, with the lack of this support associated with poor outcome [7]. Partnered sexuality and satisfaction with it may reduce exposure to stress, modify response to stress and promote recovery from stress, thereby reducing the risk of cardiovascular disease [8].…”
Section: Abdul Kader Mohiuddinmentioning
confidence: 99%